Success Guidelines: Proteksi Ruang Emosi dan Pikiran - Lia Fitriani; Masduki Asbari; Roy Cahya Wijaya (Journal of Information Systems and Management (JISMA), 2023)
This study aims to find out guidelines for success. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from Helmy Yahya's YouTube channel, entitled "To Live a Successful Life, Be Careful With Your Thoughts and Emotions" which he explained. The results of this study explain that one of the most difficult things is to maintain thoughts and emotions because these things come from each individual. Nature will support these negative thoughts and emotions if you cannot think positively. Life guidelines for a more successful and happier life, avoiding actions that hinder future success.